Underutilized Fruits Research in Arid Regions: A Review - Meghwal, P R; Singh, Akath (Annals of Arid Zone, 2017)
The hot arid regions of India cover 31.7 Mha area spread in 7 states with major area in states of Rajasthan and Gujarat. These regions are characterized by low and erratic rainfall with high coefficient of variation and harsh climatic conditions. Inspite of climatic and other constraints, these regions are suitable for growing of many fruit species like ber, pomegranate, aonla, datepalm and citrus, etc. which are grown commercially. Besides these fruit crops some underutilized fruits crops mostly indigenous ones are becoming popular in arid regions on account of their diversified uses. Underutilized crops could be considered in these areas for integration in existing farming system as these crops require less inputs and can sustain the harsh climatic conditions. There are around 30 plant species in arid zone known for their edible uses out of which some 20 plant species are known for their edible fruits or as vegetables viz., kair (Capparis decidua), lasora (Cordia myxa), jhar ber (Ziziphus nummularia), pilu (Salvadora oleoides), khejri (Prosopis cineraria), phalsa (Grewia subinaequalis), bael (Aegle marmelos), karonda (Carissa carandas), fig (Ficus carica) and prickly pear (Opuntia ficus-indica) etc. These underutilized fruits have many advantages in terms of ease in growing, hardy nature and good yield even under extreme weather conditions. These crops have their own history of consumption because, local people are well aware about their nutritional and medicinal values. Thus, these crops have the potential to provide great nutritional and social benefits and it is increasingly advised that they are identified, researched and promoted in the way similar to the other commercial fruit crops. This paper reviews the work done on collection, evaluation and conservation of germplasm, ethnobotanical values, improvement, propagation, agrotechniques, post harvest management, value addition, problems encountered and researchable issues pertaining to underutilized fruit crops in arid region.